Unequal weathering: How immigrants’ health advantage vanishes over the life-course - Silvia Loi; Peng Li; Mikko Myrskylä (Journal of Migration and Health)
The weathering hypothesis implies that there is an interaction between age and race or ethnicity that results in marginalized groups experiencing a more rapid decline in health than the dominant groups. This hypothesis has been tested mostly focusing on racial and ethnic health inequalities, while less is known about weathering by immigration background. This paper aims at contributing to this strand of research by addressing four research questions: is the health of immigrants declining at a faster pace over the life-course, compared to non-immigrants? Do higher levels of education protect immigrants from accelerated ageing compared to non-immigrants? How do income and marital status affect the health trajectories of immigrants and non-immigrants? How do these patterns vary by sex? We use longitudinal survey data to estimate healthy ageing trajectories of immigrants and non-immigrants over the life-course, in the German context. We examine the roles of education, income, and marital status, separately for men and women. We find that immigrants, and especially immigrant women, have a faster health decline than non-immigrants; that high education is linked to higher levels of health, but does not protect immigrants from ageing in poorer health compared to non-immigrants; and that health disparities between immigrants and non-immigrants persist over the life-course net of the socio-economic controls, which appear to be secondary to other unobserved determinants.